PENGARUH KARAKTERISTIK WIRAUSAHA, MODAL USAHA, DAN STRATEGI PEMASARAN TERHADAP PERKEMBANGAN UMKM - Abas Kasim; Juita L D Bessie; Anthonius B Messakh; Thomas W Isliko (Universitas Nusa Cendana, 2023)
This study aims to determine the effect of entrepreneurial characteristics, capital, and marketing strategies simultaneously or partially on the development of MSMEs in Ikat weaving in SBD Regency. The sample in this study was Ikat MSMEs in SBD Regency, totaling 55 MSMEs. The data analysis technique used is multiple linear regression analysis and hypothesis testing through the t test and F test. The results of the study show that entrepreneurial characteristics and capital have a significant effect on business development, while marketing strategy has not significant effect. For this reason, MSMEs in SBD Regency must improve their marketing strategy so that they can determine the right market segment and take advantage of advances in internet technology to promote products with low promotional costs but a wide reach. Keywords: Ikat Weaving; Entrepreneurial Characteristics; Capital; Marketing Strategy; Development of MSMEs